Legal Protection of Minority Rights: Study on the Implementation of Qanun Number 6 of 2014 Concerning the Jinayat Law in Langsa City, Aceh Special Region Province - Farkhani, Farkhani; Badwan, Badwan; Berutu, Ali Geno; Zulkarnain, Zulkarnain; Irfanudin, Fahmi (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
The negative stigma against applying Islamic law or sharia has not disappeared. This stigma persists since it is accompanied by propaganda that Islamic sharia is contrary to human rights and is barbaric. Specifically, the Special Region of Aceh Province, with its special label and special autonomy based on Law No. 44 of 1999 concerning the Implementation of the Privileges of Aceh, strengthened by Law No. 18 of 2001 concerning Special Autonomy, Law No. 11 of 2006 concerning the Government of Aceh, and part of the Memorandum of Understanding (MoU) of Helsinki bargaining, is permitted to apply Islamic law, including the issue of jinayat. This research’s object was the implementation of Qanun Jinayat in Langsa City to find out how it is implemented and how it protects the rights of minorities. Included in the field research category, this study used qualitative methods with data collection techniques through in-depth interviews and field observations. The result revealed that the enforcement of the Qanun Jinayat in Langsa City is concerned about human rights norms, does not interfere with the rights of minorities, and they even feel happy since the Qanun’s norm is also regulated in their holy book.